Effect of donor and acceptor dopants on fatigue properties in PZT thin films - Sreesattabud T. (2014)
Fatigue properties of Pb(Zr0.52Ti0.48)O3 or PZT thin films on platinized silicon substrates were investigated. Small amounts of WO3 and CuO nano-particles were added into PZT films, which showed the results of soft and hard doping characteristics, respectively. The additions also affected the fatigue properties of PZT by showing almost no hysteresis fatigue up to 108 switching bipolar pulse cycles, while the fatigue of PZT started at 106 cycles. The results suggest that the soft and hard doping could reduce the fatigue of PZT films and the oxygen vacancies play an important role in polarization degradation of the films. © 2012 Elsevier Ltd and Techna Group S.r.l.